PERAN JURU TIMBANG DALAM PENINGKATAN KUALITAS PELAYANAN KEMETROLOGIAN DI PASAR TRADISIONAL KABUPATEN PROBOLINGGO - Rini, Dyah Setyo; Natsir, Mohammad (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
ABSTRACT This study aims to find out how the role of Juru Timbang is in improving the quality of metrological services in traditional markets and to identify what factors support and hinder the implementation of the role of Juru Timbang. The research method used in this research is a quantitative descriptive method. By using a sample obtained from a population consisting of Juru Timbang, customer, market coordinators, and metrological service officers. while the data collection technique is in the form of primary data obtained from questionnaires and secondary data from report documents at UPT Legal Metrology Probolinggo Regency. The results of this study indicate that the role of Juru Timbang in Probolinggo Regency has been running very well and has made a good contribution to improving metrological services in traditional markets, although there are several things that need attention, namely related to the Juru Timbang expertise in testing measuring instruments and the speed of Juru Timbang in responding to complaints Customer.